Haemaphysalislongicornis ticks are unable to transstadially transmit Theileria haneyi to horses - Poh, Karen C.; Oyen, Kennan; Onzere, Cynthia K.; Kappmeyer, Lowell S.; Bastos, Reginaldo G. (Frontiers in Veterinary Science, 2025)
IntroductionThe recent discovery of Theileria haneyi, a tick-borne hemoparasite that causes mild clinical signs of equine piroplasmosis, has added complexity to the diagnosis of this reportable disease, which is prevalent among equids globally. Knowledge gaps regarding competent tick vectors that can transmit T. haneyi and the recent outbreak of Haemaphysalis longicornis in the US has prompted us to conduct this study. Our objective was to investigate whether H. longicornis can transstadially transmit T. haneyi to horses.Materials and methodsHaemaphysalis longicornis larvae (0.5 g) and nymphs (n = 500) were fed on a splenectomized T. haneyi-infected horse for parasite acquisition. During the tick feeding period, parasitemia was monitored using nested PCR (nPCR) and blood smear analysis. The acquisition ticks fed until repletion and were transferred to an incubator for molting. Concomitantly, red blood cells (RBCs) were collected from the acquisition horse for further infection. Freshly molted nymphs (n = 282) and adults (n = 212), 22 offsprings of the acquisition larvae and nymphs, respectively, were placed on two individual naïve spleen-intact horses for transstadial parasite transmission. Another naïve horse was inoculated with 1 mL of RBCs from the acquisition horse. After tick infestation and RBC inoculation, the transmission horses were monitored for 38 days for the presence of T. haneyi DNA in their peripheral blood using nPCR, as well as for any clinical signs of infection.Results and discussionThe splenectomized acquisition horse developed canonical signs of acute T. haneyi infection during tick acquisition. The percentage of parasitized RBCs in the acquisition horse varied between 2.2 and 8.1% during the tick feeding stage. Out of a subset of 10 engorged larvae that fed on the acquisition horse, all ticks tested nPCR positive for T. haneyi. However, only 4 out of 10 engorged nymphs that fed on the acquisition horse tested PCR positive for T. haneyi. We found no evidence for the presence of parasite DNA in the transmission ticks or in the horse’s blood nor did we observe any clinical signs of T. haneyi infection in the transmission horses. In contrast, the horse inoculated with RBCs from the acquisition horse tested nPCR positive for T. haneyi 15 days after inoculation. It showed parasites in blood smear and developed canonical clinical signs of acute infection.ConclusionThe findings show that H. longicornis ticks cannot transstadially transmit T. haneyi to horses.